Truth and words - Ebbs, Gary. (Oxford : Oxford University Press, 2009)
To clarify and facilitate our inquiries we need a theory of truth predication that applies both to sentences that we are using ourselves and to sentences used by others. Ebbs presents a new conception of words and shows how to use it to define a truth predicate that directly applies to all these kinds of sentences.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Truth; Predicate (Logic); Language and logic; Grammar, Comparative and general -- Sentences